2016
DOI: 10.1109/tmi.2016.2528120
|View full text |Cite
|
Sign up to set email alerts
|

AggNet: Deep Learning From Crowds for Mitosis Detection in Breast Cancer Histology Images

Abstract: The lack of publicly available ground-truth data has been identified as the major challenge for transferring recent developments in deep learning to the biomedical imaging domain. Though crowdsourcing has enabled annotation of large scale databases for real world images, its application for biomedical purposes requires a deeper understanding and hence, more precise definition of the actual annotation task. The fact that expert tasks are being outsourced to non-expert users may lead to noisy annotations introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
306
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 533 publications
(318 citation statements)
references
References 27 publications
0
306
0
Order By: Relevance
“…Many works add features derived from deep networks to existing feature sets or compare (2013) Detection of basal cell carcinoma H&E Convolutional auto-encoder neural network Malon and Cosatto (2013) Mitosis detection H&E Combines shapebased features with CNN Wang et al (2014) Mitosis detection H&E Cascaded ensemble of CNN and handcrafted features Ferrari et al (2015) Bacterial colony counting Culture plate CNN-based patch classifier Ronneberger et al (2015) Cell segmentation EM U-Net with deformation augmentation Shkolyar et al (2015) Mitosis detection Live-imaging CNN-based patch classifier Song et al (2015) Segmentation of cytoplasm and nuclei H&E Multi-scale CNN and graph-partitioning-based method Xie et al (2015a) Nucleus detection Ki-67 CNN model that learns the voting offset vectors and voting confidence Xie et al (2015b) Nucleus detection H&E, Ki-67 CNN-based structured regression model for cell detection Akram et al (2016) Cell segmentation FL, PC, H&E fCNN for cell bounding box proposal and CNN for segmentation Albarqouni et al (2016) Mitosis detection H&E Incorporated 'crowd sourcing' layer into the CNN framework Bauer et al (2016) Nucleus classification IHC CNN-based patch classifier Chen et al (2016b) Mitosis detection H&E Deep regression network (DRN) Gao et al (2016e) Nucleus classification IFL Classification of Hep2-cells with CNN Han et al (2016) Nucleus classification IFL Classification of Hep2-cells with CNN Janowczyk et al (2016b) Nucleus segmentation H&E Resolution adaptive deep hierarchical learning scheme Kashif et al (2016) Nucleus detection H&E Combination of CNN and hand-crafted features Mao and Yin (2016) Mitosis detection PC Hierarchical CNNs for patch sequence classification Mishra et al (2016) Classification of mitochondria EM CNN-based patch classifier Phan et al (2016) Nucleus classification FL Classification of Hep2-cells using transfer learning (pre-trained CNN) Romo-Bucheli et al (2016) Tubule nuclei detection H&E CNN-based classification of pre-selected candidate nuclei Sirinukunwattana et al (2016) Nucleus detection and classification H&E CNN with spatially constrained regression Song et al (2017) Cell segmentation H&E Multi-scale C...…”
Section: Chestmentioning
confidence: 99%
“…Many works add features derived from deep networks to existing feature sets or compare (2013) Detection of basal cell carcinoma H&E Convolutional auto-encoder neural network Malon and Cosatto (2013) Mitosis detection H&E Combines shapebased features with CNN Wang et al (2014) Mitosis detection H&E Cascaded ensemble of CNN and handcrafted features Ferrari et al (2015) Bacterial colony counting Culture plate CNN-based patch classifier Ronneberger et al (2015) Cell segmentation EM U-Net with deformation augmentation Shkolyar et al (2015) Mitosis detection Live-imaging CNN-based patch classifier Song et al (2015) Segmentation of cytoplasm and nuclei H&E Multi-scale CNN and graph-partitioning-based method Xie et al (2015a) Nucleus detection Ki-67 CNN model that learns the voting offset vectors and voting confidence Xie et al (2015b) Nucleus detection H&E, Ki-67 CNN-based structured regression model for cell detection Akram et al (2016) Cell segmentation FL, PC, H&E fCNN for cell bounding box proposal and CNN for segmentation Albarqouni et al (2016) Mitosis detection H&E Incorporated 'crowd sourcing' layer into the CNN framework Bauer et al (2016) Nucleus classification IHC CNN-based patch classifier Chen et al (2016b) Mitosis detection H&E Deep regression network (DRN) Gao et al (2016e) Nucleus classification IFL Classification of Hep2-cells with CNN Han et al (2016) Nucleus classification IFL Classification of Hep2-cells with CNN Janowczyk et al (2016b) Nucleus segmentation H&E Resolution adaptive deep hierarchical learning scheme Kashif et al (2016) Nucleus detection H&E Combination of CNN and hand-crafted features Mao and Yin (2016) Mitosis detection PC Hierarchical CNNs for patch sequence classification Mishra et al (2016) Classification of mitochondria EM CNN-based patch classifier Phan et al (2016) Nucleus classification FL Classification of Hep2-cells using transfer learning (pre-trained CNN) Romo-Bucheli et al (2016) Tubule nuclei detection H&E CNN-based classification of pre-selected candidate nuclei Sirinukunwattana et al (2016) Nucleus detection and classification H&E CNN with spatially constrained regression Song et al (2017) Cell segmentation H&E Multi-scale C...…”
Section: Chestmentioning
confidence: 99%
“…In total, they achieve best performance regarding recall, precision and f-score compared against logistic regression, SVMs, and CNNs. The importance of CNNs in medical applications is also apparent from their use within other applications such as nucleus segmentation [28], polyp detection in colonoscopy videos [15], microcalcification detection in digital breast tomosynthesis [22], mitosis detection in breast cancer histology [1], and short-term breast cancer risk prediction [19]. Our work is delimited to the aforementioned research as in contrast to the classification of a state (e.g., healthy or consolidation, type of tissue), we aim at classifying both, anatomical structures and surgical actions.…”
Section: Related Workmentioning
confidence: 99%
“…It has been shown that anonymous untrained individuals from an online community are able to generate training data of expert quality. Similar achievements were made in other biomedical imaging fields such as histopathological image analysis [2]. A remaining problem, however, is that object segmentation from scratch is relatively time-consuming and thus expensive compared to other tasks outsourced to the crowd.…”
Section: Introductionmentioning
confidence: 60%